Comparative effectiveness of parallel and recurrent calculations in combinatorial algorithms of inductive modelling - Yefimenko, S. (Індуктивне моделювання складних систем, 2013)
The paper investigates comparative effectiveness of parallel implementation and recurrent parameters estimation in combinatorial GMDH algorithm. The test experiments on run-time comparison of these two approaches for enhancing the efficiency of combinatorial algorithm are carried out. The results of these experiments confirm effectiveness of the recurrent algorithm. У роботі виконано порівняльне дослідження двох способів підвищення ефективності комбінаторного алгоритму МГУА – розпаралелювання обчислень за допомогою кластерних систем та рекурентного обчислення параметрів моделей. Проведено тестові експерименти з порівняння часу виконання відповідних алгоритмів, які показали високу ефективність рекурентного алгоритму. В работе выполнено сравнительное исследование двух способов повышения эффективности комбинаторного алгоритма МГУА – распараллеливания вычислений с помощью кластерных систем и рекуррентного вычисления параметров моделей. Проведены тестовые эксперименты по сравнению времени выполнения соответствующих алгоритмов, которые показали высокую эффективность рекуррентного алгоритма.